Development of KASP Markers and Identification of a QTL Underlying Powdery Mildew Resistance in Melon (Cucumis melo L.) by Bulked Segregant Analysis and RNA-Seq - Cao, Yanyan; Diao, Qiannan; Chen, Youyuan; Jin, Haijun; Zhang, Yongping; Zhang, Hongmei (Frontiers in Plant Science, 2021)
Powdery mildew (PM), caused by Podosphaera xanthii (Px), is one of the most devastating fungal diseases of melon worldwide. The use of resistant cultivars is considered to be the best and most effective approach to control this disease. In this study, an F2 segregating population derived from a cross between a resistant (wm-6) and a susceptible cultivar (12D-1) of melon was used to map major powdery mildew resistance genes using bulked segregant analysis (BSA), in combination with next-generation sequencing (NGS). A novel quantitative trait locus (QTL) named qCmPMR-12 for resistance to PM on chromosome 12 was identified, which ranged from 22.0 Mb to 22.9 Mb, and the MELO3C002434 gene that encodes an ankyrin repeat-containing protein was considered to be the most likely candidate gene that was associated with resistance to PM. Moreover, 15 polymorphic SNPs around the target area were successfully converted to Kompetitive Allele-Specific PCR (KASP) markers (P < 0.0001). The novel QTL and candidate gene identified from this study provide insights into the genetic mechanism of PM resistance in melon, and the tightly linked KASP markers developed in this research can be used for marker-assisted selection (MAS) to improve powdery mildew resistance in melon breeding programs.